Dual regulation of Arabidopsis AGO2 by arginine methylation - Po Hu (Nature Portfolio, 2019)
AGO2 is a core component of the RNAi machinery and contributes to plant immunity during bacterial infection. Here the authors show that AGO2 activity is suppressed by arginine methylation which not only promotes AGO2 degradation but also recruits TSN proteins to degrade AGO2-associated small RNAs.